Rethinking school violence : theory, gender, context - Saltmarsh, Sue; Robinson, Kerry; Davies, Cristyn (Palgrave Macmillan, 2020)
Taking a sociocultural approach to understanding violence, the authors in this collection examine how norms of gender, culture and educational practice contribute to school violence, providing strategies to intervene in and address violence in educational contexts